Effect of Dietary Inclusion of Neem Leaf Powder on Growth Performance, Nutrient Utilization, and Haemato-Biochemical Parameters of Japanese Quail - Prakash, Bhanu; Mondal, Bidhan C.; Palod, Jyoti; Kumar, Anil; Manjulata; Kumar, Ripusudan (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A feeding trial was conducted to discern the influence of dietary incorporation of neem (Azadirachta indica) leaf powder on growth  performance and haemato-biochemical parameters ofJapanese quail for 6 weeks. A metabolic trial was conducted during the last week  of the feeding trial to assess nutrient utilization. A total number of 144-day-old chicks of Japanese quail were randomly assigned into  four treatment groups, with 36 Japanese quail per treatment having three replicates of 12 birds each. Birds of treatment T1 (control  group ) were fed a basal diet (starter and finisher), whereas in treatment groups T2, T3, and T4, the basal diet was incorporated with  0.25%, 0.50%, and 1.00% neem leaf powder, respectively. Results showed supplementation of 0.25% neem leaf powder improved the  performance of Japanese quail in terms of body weight gain and performance index during the whole trial period. Nutrient utilization  among various treatment groups was similar. The hematological values showed no significant a lterations i n d ifferent groups. Th e  biochemical attributes among the treatment groups were similar, but a considerable decrease in the level of cholesterol and glucose was  observed with an increasing level of neem leaf powder in the diet. Activities of ALT, AST, and ALP were lowest in the T4 group. It can be  concluded that 1 percent neem leaf powder can be supplemented in feed for good health status and desired performance of the birds.
Keywords: Growth performance; Haemato-biochemical parameters; Japanese quail; Neem leaf powder; Nutrient utilization